Unraveling plant adaptation to nitrogen limitation from enzyme stoichiometry aspect in Karst soils: a case study of Rhododendron Pudingense - Wang, Haodong; Huang, Baoxian; Zhao, Hongjiu; Dai, Xiaoyong; Chen, Meng; Ding, Fangjun; Wu, Peng; Hao, Lei; Yang, Rui; Yuan, Congjun (Frontiers in Plant Science, 2023)
Enzyme stoichiometry can reflect the resource limitation of soil microbial metabolism, and research on the relationships between plants and resource limitation in Karst Microhabitats is scarcely investigated. To clarify the extracellular enzyme stoichiometry characteristics in soil across different karst microhabitats and how the Rhododendron pudingense adapts to nutrient restrictions, plot investigation experiments were set up in Zhenning County, Qinglong County, and Wangmo County of Guizhou Province which included total three karst microhabitats, i.e., soil surface (SS), rock gully (RG), and rock surface (RS), by analyzing he rhizosphere soil nutrient, extracellular enzyme activity, and nutrient content of R. pudingense. The findings indicated that all karst microenvironments experienced varying levels of nitrogen (N) limitation, with the order of N limitation being as follows: SS > RG > RS.Notably, there were significant discrepancies in N content among different plant organs (p < 0.05), with the sequence of N content as follows: leaf > stem > root.However, no significant differences were observed in nutrient content within the same organ across different microenvironments (p > 0.05). A noteworthy discovery was the significant allometric growth relationship between C-P in various organs (p < 0.05), while roots and stems exhibited a significant allometric growth relationship between N-P (p < 0.05). The study highlighted the substantial impact of Total Nitrogen (TN) and N-acquiring enzymes (NAE) on nutrient allocation within the components of R. pudingense. Overall, the research demonstrated that N was the primary limiting factor in the study area's soil, and R. pudingense's nutrient allocation strategy was closely associated with N limitations in the karst microenvironment. Specifically, the plant prioritized allocating its limited N resources to its leaves, ensuring its survival. This investigation provided valuable insights into how plants adapt to nutrient restrictions and offered a deeper understanding of soil-plant interactions in karst ecosystems.